Secondary animal science curriculum revision - Wolsdorf, Hannah (My University, 2015)
The Montello School District animal science curriculum needed to be revised in order to meet new educational initiatives set forth by the district and the State of Wisconsin. One major change include aligning course objectives with the Wisconsin Standards for Agriculture, Food, and Natural Resources and Wisconsin Common Core State Standards for Literacy in all Subjects. The focus of this project was to create an 18-week curriculum to prepare Montello students for college and career success that can also be used in other agricultural programs in Wisconsin with an animal science class. A backward design process was used to ensure that learning and assessment activities address all target standards. This curriculum incorporates topics from the animal systems section of the Wisconsin Agriculture, Food, and Natural Resources Standards into six specified units: History and Use of Animals, Animal Handling and Safety, Animal Products, Marketing, and Selection, Animal Nutrition, Animal Reproduction, and Animal Health. Each unit was broken down into performance indicators, essential questions, activities, assessments, and literacy standards. Each unit has two literacy standards identified so that the students are exposed to different literacy strategies throughout the curriculum. The curriculum layout is set up to support a future conversion to standards based grading. Formative and summative assessments included in each unit support student learning and document student mastery of each standard. The standards based curriculum developed through this project teaches students skills that will prepare them for post-secondary education or the workforce and help ensure that each student is successful upon high school graduation.
Plan B Paper. 2015. Master of Science-Agricultural Education--University of Wisconsin-River Falls. Agricultural Education Department. 15 leaves. Includes bibliographical references (leaf 15).
Keywords: Agricultural education--Wisconsin; Agriculture--Study and teaching (Secondary)--Wisconsin; Curriculum planning--Wisconsin